INFLUENCE OF PLANTING METHODS AND INTEGRATED NUTRIENT MANAGEMENT PRACTICES ON YIELD ATTRIBUTES, YIELD AND ECONOMICS OF RICE - G. PADMAJA; A. SIVA SANKER, P. REVATHI, K.B. SUNEETHA DEVI, B. GOPAL REDDY, V. PRAVEEN RAO (The Journal of Research, PJTSAU, 2019)
A field experiment was conducted during kharif Season of 2010-11and 2011-12 at AICRP on Rice, Agricultural Research Institute (ARI), Rajendranagar, Hyderabad to evaluate different planting methods (SRI, Yangio - China, Kobota transplanter and farmers method) and integrated nutrient management (INM) practices viz.,100% RDF, (150 : 60 : 40 kg N, P2 O5 & K2O ha-1), FYM, GLM @ 5 t ha-1, bio-fertiliser (Azospirillum @ 2.5 kg ha-1+ PSB @ 5 kg ha-1) along with 100% RDF. The higher mean grain, straw yield and B:C ratio (average of two years) was recorded with machine (Kobota) transplanting (7.0, 16.02 t ha-1 & 2.20) followed by farmers method (manual) of planting (6.30, 13.32t ha-1 & 2.00) and was found on par to SRI method (5.8,11.40 t ha-1 & 1.60). The lowest mean grain, straw yield and B:C was obtained with Yangio-China transplanter (5.20, 8.42 t ha-1 & 1.30). Among the INM practices greater mean grain, straw yield and B:C ratio values were registered with application of 100% RDF + FYM @ 5 ha-1 (6.90, 15.60 ha-1 & 2.00) over other INM treatments. Application of GLM @ 5 ha-1 + RDF produced higher mean grain and straw yield (6.40 and 13.30 t ha-1) and B:C ratio (1.80) followed by RDF + BF 7.5 kg ha-1). Significant interaction effect was obtained in straw yield & B:C ratio (Pooled mean). Transplanting of rice with Kobota transplanter along with application of FYM @ 5 t ha-1 + RDF (M3I 1) was found significant in recording more straw yield (19.67 t ha-1) and B:C ratio (2.40) as compared to other treatment combinations followed by the combination of farmers method of planting along with RDF + FYM @ 5 t ha-1 (M4I 1) (17.57 t ha-1 and 2.37).